A inovação no Ensino Médio na percepção dos atores escolares do Colégio Loyola - Soares, Ciro Pablo Costa (Universidade do Vale do Rio dos Sinos, 2024)
This research had the general objective of verifying how innovation in teaching occurs in the perception of students, teachers and families of high school students who have not yet been reformed according to the BNCC, from Colégio Loyola, from the Jesuit Education Network, located in Belo Horizonte/MG. To this end, a case study was carried out with a mixed approach, using semi-structured questionnaires to the students, teachers and parents included in the study. For the analysis of closed questions, quantitative responses were obtained and analyzed using descriptive statistics, while qualitative data from open questions were interpreted using content analysis. As a result, the responses demonstrated that teachers, students and families have the perception that secondary education at Colégio Loyola is in the progress phase of educational innovation, being subject to improvements depending on class models for greater student participation, continued training or improvements to teachers regarding the use of new educational technologies, so that, faced with these changes, they can break away from the traditional system, as mentioned by parents. There was a consensus among respondents regarding the resource infrastructure and promotion of education as one of the institution's highlights, however, they mentioned that human resources need to be better allocated. For these resolutions, an intervention proposal was prepared with the creation of a Pedagogical Innovations Hub in order to encourage the participation of the entire school community, including parents. Therefore, research can help in resolving obstacles to effective innovation for students in the digital era, as well as serving as an example so that managers can improve their strategies in future advents.
Keywords: Inovação pedagógica; Ensino médio; Tecnologias digitais; Práticas pedagógicas; Pedagogical innovation; High school; Digital technologies; Pedagogical practices; ACCNPQ::Ciências Humanas::Educação